1997
DOI: 10.1038/bjc.1997.300
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression of CCNDI and RBI in resection margin epithelia of lung cancer patients

Abstract: Summary Tumours develop through the accumulation of genetic alterations associated with a progressive increase of the malignant phenotype. In lung cancer, chronic exposure of bronchial epithelium to carcinogens in cigarette smoke may lead to multiple dysplastic and hyperplastic lesions scattered throughout the tracheobronchial tree. Little is known about the genetic alterations in such lesions. This study was carried out to examine cyclin Dl (CCND1) and retinoblastoma (RB1) gene expression in the bronchial epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 36 publications
5
25
0
Order By: Relevance
“…As other authors observed, the intensity of Ki67 expression is also higher in dysplasia. This way, we reinforce the utility of Ki67 as a biomarker, namely for dysplasia, as it appears as a group characterized by high proliferative index, subscribing the literature and other authors' study of preneoplastic lesions [22][23][24][25][26]59]. P53, the "guardian" maintaining the integrity of the genome by participating in the DNA damage checkpoints in the cell cycle, regulating cellular proliferation and apoptosis [20], has been detected in preneoplastic lesions of the lung, suggesting that it occurs early during lung carcinogenesis [14,18,20] as the obtained results confirmed.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As other authors observed, the intensity of Ki67 expression is also higher in dysplasia. This way, we reinforce the utility of Ki67 as a biomarker, namely for dysplasia, as it appears as a group characterized by high proliferative index, subscribing the literature and other authors' study of preneoplastic lesions [22][23][24][25][26]59]. P53, the "guardian" maintaining the integrity of the genome by participating in the DNA damage checkpoints in the cell cycle, regulating cellular proliferation and apoptosis [20], has been detected in preneoplastic lesions of the lung, suggesting that it occurs early during lung carcinogenesis [14,18,20] as the obtained results confirmed.…”
Section: Discussionmentioning
confidence: 84%
“…[18][19][20]. Those genomic and molecular abnormalities are early events in lung carcinogenesis and can persist in bronchial lesions for months or years and their persistence or regression have been correlated with lesions' evolution [15,[21][22][23][24][25][26][27][28][29][30]. Molecular changes are recognized not only in lung cancer, but also in bronchial epithelium and parenchyma of current and former smokers without the development of lung cancer [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The basal cells are multipotent reserve cells that retain the capacity to generate the various differentiated cell types of the airway epithelium. NSCLCs arise from a component(s) of this airway epithelium and it is generally possible to identify a range of pre-neoplastic lesions in the bronchial epithelia of patients, particularly smokers (Betticher et al, 1997;Ratschiller et al, 2003). Examination of multiple tumour-free sites from 20 patients allowed us to make two potentially significant observations related to the pathological expression of maspin.…”
Section: Discussionmentioning
confidence: 99%
“…(6,7). Overexpression of cyclin D1 is a frequent and early step in lung carcinogenesis (8)(9)(10)(11). Cyclin D1 overexpression is often associated with gene amplification (12) as well as allele-specific expression imbalance (11).…”
Section: Introductionmentioning
confidence: 99%